Integrasi SSI dan Metode Debat dalam Pembelajaran Biologi untuk Meningkatkan Kemampuan Berpikir Reflektif Peserta Didik pada Topik Pencemaran Lingkungan - Dian Pangestuti; Suyitno Aloysius (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to examine the effectiveness of integrating the Socio-Scientific Issues (SSI) approach and debate method in biology learning to improve students' reflective thinking skills on the topic of environmental pollution. The method used was a quasi-experimental design with a non-equivalent control group design. The research results were analyzed using N-Gain scores and an Independent Sample T-Test. The results showed a significant increase in students' reflective thinking skills after implementing the integration of SSI and debate (t = –5.857; sig. = 0.000). In conclusion, the integration of the SSI approach and debate method has a positive impact on the development of students' reflective thinking skills, especially on the topic of environmental pollution.   Keywords: Biology, Debate, Environmental pollution, Reflective thinking, SSI